Continuous Global Improvement of Human Papillomavirus (HPV) Genotyping Services : The 2022 and 2023 HPV LabNet International Proficiency Studies - Arroyo Mühr, Laila Sara; Eklund, Carina; Lagheden, Camilla; Yilmaz, Emel; Forslund, Ola; Lilja, Marina; Dillner, Joakim (Journal of Medical Virology, 2024)
The International Human Papillomavirus (HPV) Reference Center launches annual global HPV genotyping proficiency panels to enhance the precision and international standardization of HPV genotyping services. This study aims to assess the proficiency levels achieved in the global HPV genotyping proficiency panels conducted in 2022 and 2023, and to evaluate trends in performance over time. The proficiency panels comprised 44 blinded samples each, including 40 samples containing various purified plasmids corresponding to HPV types combined with human DNA, plus four control samples (one negative control and three extraction controls). Proficiency required a sensitivity of 50 International Units (IU)/5 µL for HPV 16 and HPV 18 500 IU/5 µL for HPVs 6, 11, 31, 33, 45, 52, and 58 and 500 genome equivalents (GE)/5 µL for other HPV types in both single and multiple infections, while avoiding false positivity. In 2022, 78 laboratories submitted a total of 154 data sets, and in 2023, 81 laboratories contributed 141 data sets. Most data sets (87%, 258/295) utilized commercially available HPV assays. Proficiency was common, with 77% of data sets meeting the proficiency criteria in 2022 and 79% in 2023. False positive results significantly decreased from 22% in 2022 to 13% in 2023. The high proficiency and increasing specificity in HPV genotyping services indicates progress toward more reliable HPV testing. High accuracy is crucial for supporting global efforts in HPV and cervical cancer elimination.
Keywords: human papillomavirus; International HPV Reference Center; international standards; proficiency panels; proficiency studies